Empowerment of Posyandu Cadres by The Village Government in Improving The Health of The People Of Sindangsari Village Ciranjang District - Ahmad Miftahudin (Westscience Press, 2023)
Posyandu Cadre is a Public Health Cadre whose job is under the auspices of the Village government, where the task is to assist Village Midwives in serving people in rural areas. Because Posyandu Cadres have a mission to improve the quality of public health, reduce maternal and child mortality during childbirth and improve maternal health during pregnancy. The author of this scientific paper aims to find out how the efforts of the Village Government in improving the health of its community through the empowerment of Posyandu cadres, while this research uses qualitative methods, with data collection through interviews, observations and documentation studies conducted in Sindangsari Village, Ciranjang District, Cianjur Regency. The results showed that so far, the performance of Posyandu cadres is at a moderate level, although in terms of human resources and the responsiveness of Posyandu cadres when handling mothers who give birth still have to be addressed by Village Midwives, the empowerment of Posyandu cadres by the Village Government is carried out by dividing Working Groups where in each Keerwean (Rw) there is one Posyandu. The conclusion of this study is that the Village Government's efforts in improving public health through the empowerment of Posyandu cadres are quite good and the Village Government must be more active in socializing the importance of maintaining health to the community.